Resting heart rate is associated with renal disease outcomes in patients with vascular disease: results of the ONTARGET and TRANSCEND studies - Boehm, M.; Schumacher, H.; Schmieder, Roland; Mann, J. F. E.; Teo, K.; Lonn, E.; Sleight, P.; Mancia, G.; Linz, D.; Mahfoud, F.; Ukena, C.; Sliwa, K.; et al. (Journal of Internal Medicine, 2015)
Resting heart rate (RHR) is associated with cardiovascular disease outcomes in high-risk patients. It is not known whether RHR is predictive of renal outcomes such as albuminuria, end-stage renal disease (ESRD) or doubling of creatinine. We evaluated whether RHR could predict renal endpoints in patients at a high risk of cardiovascular disease. We also tested the effects of RHR at different levels of systolic blood pressure (SBP).We analysed data from 28 757 patients in the ONTARGET and TRANSCEND trials. RHR and SBP were available for a mean of 4.9 ± 0.4 visits (range 3-5) within the first 2 years of the studies. Albuminuria was determined at baseline, at 2 years and at study end.Mean RHR was predictive of incident micro-albuminuria [hazard ratio (HR) for RHR >=80 vs. <60 beats min(-1) 1.49, 95% confidence interval (CI) 1.29-1.71, P < 0.0001], incident macro-albuminuria (HR 1.84, 95% CI 1.39-2.42, P < 0.0001), doubling of creatinine (HR 1.47, 95% CI 1.00-2.17, P = 0.050) and ESRD (HR 1.78, 95% CI 1.00-3.16, P = 0.050), and the combined renal end-point (HR 1.51, 95% CI 1.32-1.74, P < 0.0001). Associations were robust at SBPs from <120 to >=150 mmHg, with the lowest risk at a SBP of 130-140 mmHg.Resting heart rate is a potent predictor of these renal outcomes, as well as their combination, in patients with cardiovascular disease. RHR at all SBP levels should be considered as a possible renal disease risk predictor and should be investigated as a treatment target with RHR-reducing agents.
EVALuna2:3749